The implementation of green marketing as a modern dimension of corporate social responsibility to achieve sustainable development: Global experiences in adopting the concept of green marketing - Assia, Hamoudi; Fatiha, Bentaiba (The International tax journal, 2025)
This article presents a study of argumentative discourse in narratives, applying a pragmatic approach to analyse selected models from Victor Hugo's novel Les Misérables. It begins by addressing the issue of the adoption of modern critical frameworks in the Arab context, where, according to the author, these frameworks are accepted unconditionally without any filtering or scrutiny. In this regard, the pragmatic approach emerges as a procedural tool capable of exploring the argumentative structures embedded within literary discourse while addressing the reservations raised about its applicability to narrative texts. Focusing on the analysis of direct and indirect speech acts, as well as the argumentative connections in the chapter 'The Struggles of Jean Valjean', the article draws on the theories of Austin, Searle, Ducrot and Enscumber, as well as Hafiz Ibrahim's translation of the novel. The analysis reveals how these pragmatic mechanisms contribute to the text's persuasive dimension, emphasising society's harshness towards the protagonist and his journey of repentance and moral transformation. The article concludes that the pragmatic approach significantly activates the novel's argumentative potential, emphasising that its effectiveness is demonstrated through application rather than strict adherence to its propositions.